PENGARUH CORPORATE GOVERNANCE TERHADAP TINGKAT PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DI BANK SYARIAH - Dwi Sudaryati; Yunita Eskadewi (Jurnal Ekonomi Dan Bisnis, 2015)
The objective of this paper is to observe the influence of corporate governance towards the disclosurelevel of corporate social responsibility in Syariah Bank.Syariah Accounting as one of Alternative AccountingScience progressively shows growth with excitement latterly. Understanding about Syariah Accounting conceptand its applying become an important matter remember fast progressively its growth Syariah Institutions in theworld. The lifting of Corporate Governance and the disclosure of Corporate Social Responsibility are representone of reaction to issues about both the things in the world of Accountancy. Besides that, Corporate Governanceand Corporate Social Responsibility ( CSR) are represent two matter which is in line with Islam values so thatneed to be done a empirical study about applying both the things in Syariah Institution, specially in SyariahBanking.  The conclusion of this paper is Islamic Governance give the influence to the disclosure level ofCorporate Social Responsibility that presented by Syariah Bank in its Annual Financial Statement.Keywords: Corporate Governance, Corporate Social Responsibility,Syariah Bank.